2018
DOI: 10.1123/iscj.2017-0018
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ Perspectives on Personal and Psychosocial Development in University Sport

Abstract: Evidence suggests Canadian university sport programs can foster positive development. Further, university coaches have claimed to focus on their athletes’ personal and psychosocial development. Despite coaches’ claims, little is known about university coaches’ strategies for enhancing positive development. The aim of the present study was to explore the role of the coach in fostering positive development in the university context from the perspective of coaches. Specifically, this study addressed two research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
3
12
0
1
Order By: Relevance
“…Consistent with our findings, Rathwell and Young (2018) also found that establishing a caring and supportive environment helped athletes to learn from their mistakes and/or failures, and interpret them as teachable moments that may help them strive in life.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Consistent with our findings, Rathwell and Young (2018) also found that establishing a caring and supportive environment helped athletes to learn from their mistakes and/or failures, and interpret them as teachable moments that may help them strive in life.…”
Section: Discussionsupporting
confidence: 89%
“…Of interest, many coaches viewed PD as a natural by-product of sport participation and used few strategies to foster this type of outcomes. The current results contrast those found in youth sport settings (Holt et al, 2017;Turnnidge, Côté, & Hancock, 2014), but are more consistent with research on PD in university sport (Rathwell & Young, 2018). In the youth context, researchers have suggested that in order to foster PD outcomes coaches should take a deliberate approach that includes concrete objectives and activities and strategies designed to systematically pursue PD outcomes (Bean & Forneris, 2016).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…For instance, coaches influence athletes through the direct teaching of life skills (e.g. teaching goal setting) [11].…”
Section: Methodsmentioning
confidence: 99%